From Surrender to Protest Against Patriarchy in Pandey’s Jiyara - Bista, Asmita (JODEM: Journal of Language and Literature, 2022)
The anthology of stories Jiyara by Nayan Raj Pandey unveils the violence against women in Madhes. The anthology explores the plights of Madhesi women who are victimized by patriarchal agents, but the stories also depict the women who courageously fight against the impostors. So, the article investigates the problems faced by the Madhesi women in the society that is driven by patriarchy, in the stories “Jiyara” and “Laila O Laila”. It navigates the causes of the oppression, abuse, and violence against women in Madhesi community. The article analyzes the ways that are deployed by the Madhesi women to react against the patriarchy. To address these objectives, feminist theory, mainly theory of radical feminist Kate Millet has been used. Kate Millet brings up the idea that men create and maintain patriarchy because they own resources. Likewise, patriarchy helps them to enslave women. So, in order to fight for sexist exploitation and oppression, women need to reject the subordinated position set for them by patriarchal society. The significance of this study is to contribute to a different perspective for the reader to see the anthology Jiyara because in this text, Pandey highlights the problems faced by Madhesi women due to the socio-cultural practices that endorse males’ domination. The paper concludes that in “Jiyara”, major female characters get victimized by patriarchal social system, whereas the female characters of “Laila O Laila” stand starkly against the violence and suppression done to them by their male counterparts, when it transcends their tolerance.